CHARACTERISTICS OF THE QUALIFICATION OF THE CORPORATE DISPUTES IN THE CASE OF TERMINATION OF THE AUTHORITIES OF THE DIRECTOR OF THE ORGANIZATION - Khundkaryan, Henrik (State and Law, 2024)
The article analyzes the borders, problems and characteristics of the ratio of labor and corporate disputes in the case of the termination of the authority of the director of the organization (resolving the employment contract). As a result of the study, the special status of the director of the organization was emphasized due to the agent-principal relationship between the director of the organization and the organization as a subject of corporate law. The work also touched upon the features by which the labor dispute differs from other civil law disputes. The solution proposed as a result of the study will lead to the elimination of the contradictions in the judicial practice (including domestic case law) formed in the cases of termination of the authority of the director of the organization.
Keywords: labor dispute; conflict; corporate dispute; labor contract; characteristics of labor dispute; termination of director's duties; agent; fiduciary duty